Highly hydrophilic microfluidic device prototyping using a novel poly(dimethylsiloxane)-based polymeric mix1. Issue 10 (6th February 2015) - Rigat-Brugarolas, L. G.; Homs-Corbera, A.; Samitier, J.
<x xml:space="preserve">Abstract</x> We present a novel methodology to create in a simple and fast way an interpenetrating polymer network biomaterial, mixing 2-hydroxyethil methacrylate and poly(dimethylsiloxane), for long-lasting highlyhydrophilic microfluidic device prototyping.